Fluid Surface Damping: A Technique for Vibration Suppression of Beams - Hany Ghoneim (Shock and Vibration)
A fluid surface damping (FSD) technique for vibration suppression of beamlikestructures is proposed. The technique is a modification of the surface layer damping method. Two viscoelastic surface layers containing fluid-filled cavities are attached symmetrically to the opposite surfaces of the beam. The cavities on one side are attached to the corresponding cavities on the other side via connection passages. As the beam vibrates, the fluid is pumped back and forth through the connecting passages. Therefore, in addition to the viscoelastic damping provided by the surface layers, the technique offers viscous damping due to the fluid flow through the passage. A mathematical model for the proposed technique is developed, normalized, and solved in the frequency domain to investigate the effect of various parameters on the vibration suppression of a cantilever beam. The steady-state frequency response for a base white-noise excitation is calculated at the beam's free tip and over a frequency range containing the first five resonant frequencies. The parameters investigated are the flow-through passage viscous resistance, the length and location of the layers, the hydraulic capacitance of the fluid-filled cavities, and inertia of the moving fluid (hydraulic inertance). Results indicate that the proposed technique has promising potential in the field of vibration suppression of beamlike structures. With two FSD elements, all peak vibration amplitudes can be well suppressed over the entire frequency spectrum studied.